A BN fiber@PANI nanocomposite absorbing material and preparation method thereof
Through the nanocomposite technology of boron nitride fiber and polyaniline, the problem of degradation of existing microwave absorbing materials in high-temperature environments is solved, and the thermal stability and performance of the materials are improved, and it is suitable for microwave absorption applications in high-temperature environments.
Patent Information
- Application Number
- CN202411832925.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-13
AI Technical Summary
In long-term use and high-temperature environments, existing microwave absorbing materials are prone to deterioration in microwave absorbing performance due to loose fiber surface structure and pyrolysis or carbonization, and are insufficient in flame retardant, corrosion resistance and electrical conductivity.
The nanocomposite absorbent material is prepared by combining boron nitride fibers (BN fibers) with polyaniline (PANI). Through ice bath pre-contact and droplet addition reaction with specific ammonium persulfate solution, the uniform distribution and firm combination of polyaniline are achieved, and the thermal stability and performance of the material are improved.
It improves the thermal stability, flame retardant, corrosion resistance and electrical conductivity of microwave absorbing materials, ensures the stability of microwave absorbing properties and mechanical properties, and is suitable for high-temperature environments.
Smart Images

Figure CN119287669B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of wave absorbing materials, and in particular to a BN fiber@PANI nanocomposite wave absorbing material and a preparation method thereof. Background Art
[0002] The development of science and technology and the widespread application of wireless communication technology have brought convenience to human production and life, but also caused a large amount of electromagnetic radiation, affecting the normal operation of precision instruments and endangering human health. Nowadays, the preparation of suitable microwave absorbing materials to prevent electromagnetic waves from affecting the normal operation of complex and precise electronic equipment and reduce interference with the human body's inherent magnetic field has become a hot research issue.
[0003] In recent years, in order to solve the problem of electromagnetic pollution, people have developed a large number of microwave absorbing materials, including carbon materials, magnetic materials, polymer conductive materials and ceramic materials. In contrast, the single electromagnetic loss mechanism proves that it is very challenging for single-component microwave absorbing materials to maintain good microwave absorption performance. Therefore, composite materials with the synergistic effect of multiple loss mechanisms and well-matched impedance have become a more important research object at present. In addition, good structural design is also important for microwave absorbing materials. The unique structure allows multiple reflections of electromagnetic waves to be formed in the absorber, thereby increasing the microwave absorption properties of microwave absorbing materials.
[0004] The prior art discloses microwave absorbing materials that combine polyaniline (PANI) with cellulose fiber, bamboo fiber, ramie fiber, and carbon nanotube fiber. However, due to the loose fiber surface structure of cellulose fiber, bamboo fiber, ramie fiber, and carbon nanotube fiber, the aforementioned microwave absorbing materials are easily affected by environmental factors (such as humidity, temperature, etc.) during long-term use, causing deformation or degradation, resulting in a decrease in microwave absorbing performance; at the same time, natural fibers are prone to pyrolysis or carbonization in a high-temperature working environment, and carbon nanotube fibers will also undergo structural changes in a high-temperature working environment. The thermal stability of the microwave absorbing material is poor, which affects the composite effect of the fiber and polyaniline and the microwave absorbing performance, and directly leads to a significant decrease in microwave absorbing performance and mechanical properties. At the same time, the flame retardancy, corrosion resistance, and electrical conductivity of the above-mentioned existing microwave absorbing materials need to be further improved.
[0005] Boron nitride (BN) has high thermal stability and can maintain good structural stability and performance stability under high temperature environment. In the prior art, Zhong et al. synthesized a three-dimensional (3D) BN nanosheet (h-BNNS) decorated carbon nanotube (3D hBNNS / CNTs) composite material. Compared with carbon nanotubes, the three-dimensional h-BNNS / CNT exhibited a lower RL value and a wider EAB value. When the absorber thickness is 2.5 mm, the RLmin can reach -36.5 dB. After analysis, the significant improvement in the absorption performance of the three-dimensional h-BNNS / CNTs is mainly due to the improvement of the impedance matching and interface polarization effect of the micro-absorber material after the introduction of h-BNNS. It can be seen that studying the microwave absorption characteristics of the BN system has important prospects and technical value.
[0006] In the process of preparing microwave absorbing materials by combining boron nitride fiber (BN fiber) with polyaniline (PANI), the inventors found that due to the smooth outer surface of the boron nitride fiber and the small number of active binding sites on the fiber surface, it is impossible to ensure the uniform distribution of polyaniline on the outer surface of the boron nitride fiber, and it is also impossible to ensure the effective and firm bonding of polyaniline and the boron nitride fiber. This is a major technical difficulty in preparing microwave absorbing materials by combining boron nitride fiber with polyaniline. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a BN fiber@PANI nanocomposite absorbing material and a preparation method thereof, which can overcome the poor thermal stability of the existing microwave absorbing material combining fiber and polyaniline, affect the composite effect of fiber and polyaniline, affect its microwave absorbing performance and mechanical properties, and at the same time achieve uniform distribution of polyaniline on the outer surface of boron nitride fiber filaments, and effectively and firmly combine polyaniline and boron nitride fiber filaments; and further improve the flame retardancy, corrosion resistance and electrical conductivity of the microwave absorbing material.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a BN fiber@PANI nanocomposite wave absorbing material, the method comprising the following steps: pre-contact, reaction coating, and post-treatment;
[0010] The pre-contact method comprises: mixing aniline, hydrochloric acid solution and deionized water uniformly to obtain a pre-contact solution; placing the pre-contact solution in an ice bath, and then placing the boron nitride fiber into the pre-contact solution in the ice bath, stirring the ice bath for 1.5-2.5 hours, and obtaining a mixed contact solution;
[0011] The reaction coating method comprises the following steps: adding the ammonium persulfate solution dropwise to the mixed contact liquid in an ice bath under stirring conditions; after the ammonium persulfate solution is added dropwise, the ice bath is continued to stir and react for 4-5 hours to obtain a reaction solution;
[0012] The post-treatment method comprises filtering out the solid matter in the reaction solution, washing the solid matter with deionized water and anhydrous ethanol in sequence, and drying the solid matter to obtain the BN fiber@PANI nanocomposite wave absorbing material.
[0013] Preferably, in the pre-contact, the concentration of the hydrochloric acid solution is 0.9-1.1 mol / L;
[0014] The diameter of the boron nitride fiber is 7-9 μm.
[0015] Preferably, in the pre-contact, the mass volume ratio of the boron nitride fiber, aniline, hydrochloric acid solution and deionized water is 1 g: 100-400 μL: 4.8-5.2 mL: 50-55 mL.
[0016] Preferably, in the reaction coating, the dropping rate of ammonium persulfate is 0.8-1.6 mL / min.
[0017] Preferably, in the reaction coating, the mass volume ratio of ammonium persulfate to deionized water in the ammonium persulfate solution is 0.5-0.6 g:10 mL.
[0018] Preferably, in the reaction coating, the volume ratio of the ammonium persulfate solution to the mixed contact liquid is 1:5.5-5.8.
[0019] A BN fiber@PANI nanocomposite wave absorbing material is prepared by the above-mentioned preparation method.
[0020] Preferably, the diameter of the BN fiber@PANI nanocomposite absorbing material is 11-13 μm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The preparation method of the BN fiber @PANI nanocomposite absorbing material of the present invention comprises selecting a specific boron nitride fiber and combining it with an aniline monomer of a specific specification, and after pre-contacting in an ice bath, controlling the addition rate of a specific ammonium persulfate solution, and conducting an ice bath reaction, and then post-treating to obtain the BN fiber @PANI nanocomposite absorbing material; the aforementioned technical means cooperate with each other and work synergistically to overcome the poor thermal stability of the existing microwave absorbing materials combined with fiber and polyaniline, which affects the composite effect of fiber and polyaniline, and affects its microwave absorbing performance and mechanical properties, while achieving uniform distribution of polyaniline on the outer surface of the boron nitride fiber filaments, and effectively and firmly combining polyaniline with the boron nitride fiber filaments; and further improving the flame retardancy, corrosion resistance and electrical conductivity of the microwave absorbing material.
[0023] (2) The BN fiber@PANI nanocomposite absorbing material of the present invention has a maximum reflection loss value of -41.15 dB at a frequency of 16.64 GHz, and a matching thickness of 1.25 mm.
[0024] (3) The BN fiber@PANI nanocomposite absorbing material of the present invention has a maximum effective absorption bandwidth of 4.80 GHz at a matching thickness of 1.38 mm, and has excellent electromagnetic wave absorption performance while also having the characteristics of light weight and low density.
[0025] (4) After testing, the BN fiber @PANI nanocomposite absorbing material of the present invention was calcined at 260°C for 120 hours. At a frequency of 16.64 GHz, the strongest reflection loss value of the BN fiber @PANI nanocomposite material can still reach -40.61 dB, with a matching thickness of 1.25 mm. At a matching thickness of 1.38 mm, the widest effective absorption bandwidth can still reach 4.70 GHz. Moreover, the tensile strength and elastic modulus have no significant changes compared with those before calcination. Its electromagnetic wave absorption performance has good thermal stability in a high temperature environment. The composite effect of boron nitride fiber and polyaniline is good, which effectively avoids the poor stability of the composite absorbing material affecting the microwave absorption performance and mechanical properties.
[0026] (5) The preparation method of the BN fiber@PANI nanocomposite absorber of the present invention has a simple process, is easy to control, has a low preparation cost, has good repeatability, and is conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a microwave absorption performance diagram (reflection loss-frequency) of the BN fiber@PANI nanocomposite absorbing material of Example 1 at different matching thicknesses.
[0028] Figure 2 This is the microwave absorption performance diagram of the BN fiber@PANI nanocomposite absorbing material of Example 1 (matching thickness-frequency diagram).
[0029] Figure 3 This is a three-coordinate stereogram of the microwave absorption performance of the BN fiber@PANI nanocomposite absorbing material of Example 1 (reflection loss-frequency-matching thickness). DETAILED DESCRIPTION
[0030] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0031] Example 1
[0032] A method for preparing a BN fiber@PANI nanocomposite absorbing material, specifically comprising:
[0033] 1. Pre-contact
[0034] 100 μL of aniline, 5 mL of hydrochloric acid solution (concentration of 1 mol / L), and 50 mL of deionized water were mixed evenly to prepare a pre-contact solution; the pre-contact solution was placed in an ice bath, and the temperature of the pre-contact solution was controlled at about 0°C; then 1 g of boron nitride fiber was put into the pre-contact solution in the ice bath, and the ice bath was stirred for 2 hours to obtain a mixed contact solution.
[0035] The diameter of the boron nitride fiber is 8 μm.
[0036] 2. Reaction coating
[0037] Under stirring conditions, the ammonium persulfate solution was added dropwise to the mixed contact liquid in the ice bath at a dropping rate of 1.1 mL / min. After the addition of the ammonium persulfate solution was completed, the reaction was continued with stirring in the ice bath for 4 hours to obtain a reaction solution.
[0038] The preparation method of the ammonium persulfate solution is as follows: adding ammonium persulfate into deionized water and stirring to dissolve the solution; the mass volume ratio of ammonium persulfate to deionized water is 0.6 g:10 mL.
[0039] The volume ratio of the ammonium persulfate solution to the mixed contact liquid is 1:5.5.
[0040] 3. Post-processing
[0041] The solid matter in the reaction solution was filtered out, washed three times with deionized water and anhydrous ethanol in sequence, and then transferred into an oven and dried at 60° C. to constant weight to obtain a BN fiber@PANI nanocomposite absorbing material.
[0042] This embodiment also provides a BN fiber@PANI nanocomposite absorbing material prepared by the aforementioned method. After testing, the diameter of the BN fiber@PANI nanocomposite absorbing material is 12 μm, the tensile strength is 960 MPa, and the elastic modulus is 353 GPa.
[0043] The electromagnetic wave absorption performance of the BN fiber@PANI nanocomposite absorbing material of this embodiment was tested:
[0044] like Figure 1 , Figure 3 As shown, for the BN fiber@PANI nanocomposite absorbing material of this embodiment, when the frequency is 16.64 GHz, the strongest reflection loss value of the BN fiber@PANI nanocomposite material is -41.15 dB, and the matching thickness is 1.25 mm.
[0045] like Figure 2 , Figure 3As shown, the BN fiber@PANI nanocomposite absorbing material of this embodiment has a widest effective absorption bandwidth of 4.80 GHz at a matching thickness of 1.38 mm, and has excellent electromagnetic wave absorption performance while also having the characteristics of light weight and low density.
[0046] Further, the BN fiber @PANI nanocomposite absorbing material of this embodiment is placed in a baking furnace, and in an air atmosphere environment, the temperature is raised to 260°C at a heating rate of 5°C / min, and after being kept warm for 120 hours, it is cooled to room temperature with the furnace, and then its electromagnetic wave absorption performance is tested. The BN fiber @PANI nanocomposite absorbing material that has been standing for a long time in a high temperature environment has a strongest reflection loss value of -40.67dB at a frequency of 16.64GHz, and a matching thickness of 1.25mm; at a matching thickness of 1.38mm, the widest effective absorption bandwidth can still reach 4.73GHz, and its electromagnetic wave absorption performance is not significantly reduced compared with that before high temperature treatment, and the thermal stability in a high temperature environment is good. The composite effect of boron nitride fiber and polyaniline is good, which effectively avoids the composite absorbing material from affecting the microwave absorption performance due to poor stability. At the same time, the tensile strength and elastic modulus of the BN fiber @PANI nanocomposite absorbing material that has been standing for a long time in a high temperature environment have no significant changes compared with those before 260°C high temperature treatment.
[0047] Example 2
[0048] A method for preparing a BN fiber@PANI nanocomposite absorbing material, specifically comprising:
[0049] 1. Pre-contact
[0050] 200 μL of aniline, 4.8 mL of hydrochloric acid solution (concentration of 0.9 mol / L), and 52 mL of deionized water were mixed evenly to prepare a pre-contact solution; the pre-contact solution was placed in an ice bath, and the temperature of the pre-contact solution was controlled at about 0°C; then 1 g of boron nitride fiber was put into the pre-contact solution in the ice bath, and the ice bath was stirred for 1.5 hours to obtain a mixed contact solution.
[0051] The diameter of the boron nitride fiber is 8 μm.
[0052] 2. Reaction coating
[0053] Under stirring conditions, the ammonium persulfate solution was added dropwise to the mixed contact liquid in the ice bath at a dropping rate of 0.8 mL / min. After the addition of the ammonium persulfate solution was completed, the reaction was continued with stirring in the ice bath for 4.5 hours to obtain a reaction solution.
[0054] The preparation method of the ammonium persulfate solution is as follows: adding ammonium persulfate into deionized water and stirring to dissolve the solution; the mass volume ratio of ammonium persulfate to deionized water is 0.5 g:10 mL.
[0055] The volume ratio of the ammonium persulfate solution to the mixed contact liquid is 1:5.6.
[0056] 3. Post-processing
[0057] The solid matter in the reaction solution was filtered out, washed three times with deionized water and anhydrous ethanol in sequence, and then transferred into an oven and dried at 62° C. to constant weight to obtain a BN fiber@PANI nanocomposite absorbing material.
[0058] This embodiment also provides a BN fiber@PANI nanocomposite absorbing material prepared by the aforementioned method. After testing, the diameter of the BN fiber@PANI nanocomposite absorbing material is 12.4 μm, the tensile strength is 964 MPa, and the elastic modulus is 355 GPa.
[0059] The electromagnetic wave absorption performance of the BN fiber@PANI nanocomposite absorbing material of this embodiment was tested:
[0060] The BN fiber@PANI nanocomposite absorbing material of this embodiment has a strongest reflection loss value of -41.09 dB at a frequency of 16.64 GHz, and a matching thickness of 1.25 mm.
[0061] The BN fiber@PANI nanocomposite absorbing material of this embodiment has a maximum effective absorption bandwidth of 4.77 GHz at a matching thickness of 1.38 mm, and has excellent electromagnetic wave absorption performance while also having the characteristics of light weight and low density.
[0062] Further, the BN fiber @PANI nanocomposite absorbing material of this embodiment is placed in a baking furnace, and in an air atmosphere environment, the temperature is raised to 260°C at a heating rate of 5°C / min, and after being kept warm for 120 hours, it is cooled to room temperature with the furnace, and then its electromagnetic wave absorption performance is tested. The BN fiber @PANI nanocomposite absorbing material that has been left standing for a long time in a high temperature environment has a strongest reflection loss value of -40.61dB at a frequency of 16.64GHz, and a matching thickness of 1.25mm; at a matching thickness of 1.38mm, the widest effective absorption bandwidth can still reach 4.70GHz, and its electromagnetic wave absorption performance is not significantly reduced compared with that before high temperature treatment, and the thermal stability in a high temperature environment is good. The composite effect of boron nitride fiber and polyaniline is good, which effectively avoids the composite absorbing material from affecting the microwave absorption performance due to poor stability. At the same time, the tensile strength and elastic modulus of the BN fiber @PANI nanocomposite absorbing material that has been left standing for a long time in a high temperature environment have no significant changes compared with those before 260°C high temperature treatment.
[0063] Example 3
[0064] A method for preparing a BN fiber@PANI nanocomposite absorbing material, specifically comprising:
[0065] 1. Pre-contact
[0066] 300 μL of aniline, 5.2 mL of hydrochloric acid solution (concentration of 1.1 mol / L), and 55 mL of deionized water were mixed evenly to prepare a pre-contact solution; the pre-contact solution was placed in an ice bath, and the temperature of the pre-contact solution was controlled at about 0°C; then the boron nitride fiber was put into the pre-contact solution in the ice bath, and the ice bath was stirred for 2.5 hours to obtain a mixed contact solution.
[0067] The diameter of the boron nitride fiber is 8 μm.
[0068] 2. Reaction coating
[0069] Under stirring conditions, the ammonium persulfate solution was added dropwise to the mixed contact liquid in the ice bath at a dropping rate of 1.6 mL / min. After the addition of the ammonium persulfate solution was completed, the reaction was continued with stirring in the ice bath for 5 hours to obtain a reaction solution.
[0070] The preparation method of the ammonium persulfate solution is as follows: adding ammonium persulfate into deionized water and stirring to dissolve the solution; the mass volume ratio of ammonium persulfate to deionized water is 0.6 g:10 mL.
[0071] The volume ratio of the ammonium persulfate solution to the mixed contact liquid is 1:5.8.
[0072] 3. Post-processing
[0073] The solid matter in the reaction solution was filtered out, washed three times with deionized water and anhydrous ethanol in sequence, and then transferred into an oven and dried at 65° C. to constant weight to obtain a BN fiber@PANI nanocomposite absorbing material.
[0074] This embodiment also provides a BN fiber@PANI nanocomposite absorbing material prepared by the aforementioned method. After testing, the diameter of the BN fiber@PANI nanocomposite absorbing material is 12.9 μm.
[0075] The electromagnetic wave absorption performance of the BN fiber@PANI nanocomposite absorbing material of this embodiment was tested:
[0076] The BN fiber@PANI nanocomposite absorbing material of this embodiment has a strongest reflection loss value of -41.03 dB at a frequency of 16.64 GHz, and a matching thickness of 1.25 mm.
[0077] The BN fiber@PANI nanocomposite absorbing material of this embodiment has a maximum effective absorption bandwidth of 4.75 GHz at a matching thickness of 1.38 mm, and has excellent electromagnetic wave absorption performance while also having the characteristics of light weight and low density.
[0078] Further, the BN fiber @PANI nanocomposite absorbing material of this embodiment is placed in a baking furnace, and in an air atmosphere environment, the temperature is raised to 260°C at a heating rate of 5°C / min, and after being kept warm for 120 hours, it is cooled to room temperature with the furnace, and then its electromagnetic wave absorption performance is tested. The BN fiber @PANI nanocomposite absorbing material that has been standing for a long time in a high temperature environment has a strongest reflection loss value of -40.54dB at a frequency of 16.64GHz, and a matching thickness of 1.25mm; at a matching thickness of 1.38mm, the widest effective absorption bandwidth can still reach 4.66GHz, and its electromagnetic wave absorption performance is not significantly reduced compared with that before high temperature treatment, and the thermal stability in a high temperature environment is good. The composite effect of boron nitride fiber and polyaniline is good, which effectively avoids the composite absorbing material from affecting the microwave absorption performance due to poor stability. At the same time, the tensile strength and elastic modulus of the BN fiber @PANI nanocomposite absorbing material that has been standing for a long time in a high temperature environment have no significant changes compared with those before 260°C high temperature treatment.
[0079] Furthermore, the BN fiber@PANI nanocomposite absorbing material prepared by the preparation method of Examples 1-3 of the present invention can form a carbon layer during combustion through the carbon-bearing capacity of polyaniline uniformly bonded to the outer surface of the absorbing material, which plays a role in heat insulation and oxygen isolation, thereby preventing the spread of flames; at the same time, boron nitride has a lamellar structure similar to graphite, which can further play a barrier role and delay the transfer of heat and oxygen; the combination of boron nitride fiber and polyaniline, their synergistic effect can greatly improve the flame retardant properties of the absorbing material and its high-temperature working stability.
[0080] Furthermore, the BN fiber@PANI nanocomposite absorbing material prepared by the preparation method of Examples 1-3 of the present invention can form a stable oxidized structure through the polyaniline uniformly bonded to the outer surface of the absorbing material, effectively improving the chemical stability and corrosion resistance of the composite absorbing material.
[0081] At the same time, the BN fiber@PANI nanocomposite absorbing material prepared by the preparation method of Examples 1-3 of the present invention can effectively regulate the conductive properties of the composite absorbing material through the polyaniline uniformly bonded to the outer surface of the absorbing material through interface interaction, and can be effectively used in sensors, electronic devices and other fields, further expanding the scope of application.
[0082] It can be seen that the preparation method of the BN fiber @PANI nano-composite absorbing material of the present invention selects a specific boron nitride fiber and a specific specification of aniline monomer to combine, after ice bath pre-contact, adopts a specific ammonium persulfate solution to control the addition rate, and after ice bath reaction, post-treatment, the BN fiber @PANI nano-composite absorbing material is obtained; the aforementioned technical means cooperate with each other and work synergistically, which can overcome the poor thermal stability of the existing microwave absorbing material combined with fiber and polyaniline, affect the composite effect of fiber and polyaniline, affect its microwave absorbing performance and mechanical properties, and realize the uniform distribution of polyaniline on the outer surface of the boron nitride fiber filament, and effectively and firmly combine the polyaniline and the boron nitride fiber filament; and further improve the flame retardant, corrosion resistance and conductive properties of the microwave absorbing material.
[0083] Unless otherwise specified, all percentages used in the present invention are by mass.
[0084] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a BN fiber@PANI nanocomposite absorbing material, characterized in that: The preparation method comprises the following steps: pre-contact, reaction coating, and post-treatment; The pre-contact method comprises: mixing aniline, hydrochloric acid solution and deionized water uniformly to obtain a pre-contact solution; placing the pre-contact solution in an ice bath, and then placing the boron nitride fiber into the pre-contact solution in the ice bath, stirring the ice bath for 1.5-2.5 hours, and obtaining a mixed contact solution; In the pre-contact, the diameter of the boron nitride fiber is 7-9 μm; The concentration of hydrochloric acid solution is 0.9-1.1 mol / L; The mass volume ratio of the boron nitride fiber, aniline, hydrochloric acid solution, and deionized water is 1 g: 100-400 μL: 4.8-5.2 mL: 50-55 mL; The reaction coating method comprises the following steps: adding the ammonium persulfate solution dropwise to the mixed contact liquid in an ice bath under stirring conditions; after the ammonium persulfate solution is added dropwise, the ice bath is continued to stir and react for 4-5 hours to obtain a reaction solution; During the reaction coating, the dropping rate of the ammonium persulfate solution is 0.8-1.6 mL / min; The mass volume ratio of ammonium persulfate to deionized water in the ammonium persulfate solution is 0.5-0.6 g:10 mL; The post-treatment method comprises filtering out the solid matter in the reaction solution, washing the solid matter with deionized water and anhydrous ethanol in sequence, and drying the solid matter to obtain the BN fiber@PANI nanocomposite wave absorbing material.
2. The method for preparing the BN fiber@PANI nanocomposite absorbing material according to claim 1, characterized in that: In the reaction coating, the volume ratio of the ammonium persulfate solution to the mixed contact liquid is 1:5.5-5.
8.
3. A BN fiber@PANI nanocomposite absorbing material, characterized in that: The method is prepared according to claim 1 or 2.
4. The BN fiber@PANI nanocomposite absorbing material according to claim 3, characterized in that: The diameter of the BN fiber@PANI nanocomposite wave absorbing material is 11-13 μm.
Citation Information
Patent Citations
PANI / CoFe2O4 / Ba0.4Sr0.6TiO3 wave-absorbing material and preparation method thereof
CN105482111A
Preparation method of polyaniline / nickel-coated carbon fiber composite wave absorbing material
CN105504276A